Citizens, consumers and farm animal welfare: A meta-analysis of willingness-to-pay studies. (April 2017) - Clark, Beth; Stewart, Gavin B.; Panzone, Luca A.; Kyriazakis, Ilias; Frewer, Lynn J.
Highlights: Overall a small consumer WTP for farm animal welfare was identified. Only 4 of the 54 studies established WTP for reduced production diseases. Differences in WTP for welfare existed between animal type, regions and population. Gaps in evidence for policy development were identified. The results support the use multiple policy options for improving animal welfare. Abstract: The sustainable intensification of animal production systems is increasing as a consequence of increased demand for foods originating from animals. Production diseases are particularly endemic in intensive production systems, and can negatively impact upon farm animal welfare. There is an increasing need to develop policies regarding animal production diseases, sustainable intensification, and animal welfare which incorporate consumer priorities as well as technical assessments of farm animal welfare. Consumers and/or citizens may have concerns about intensive production systems, and whether animal production disease represent a barrier to consumer acceptance of their increased use. There is a considerable body of research focused on consumer willingness-to-pay (WTP) for improved animal welfare. It is not clear how this relates specifically to a preference for reduced animal production disease incidence in animal production systems. A systematic review and meta-analysis were conducted to establish the publics' WTP for farm animal welfare, with a focus on production diseases which arise in intensive systems. Systematic review methodology combined with data synthesis was applied to integrate existing knowledge regarding consumer WTP for animal welfare, and reduced incidence of animal production diseases. Multiple databases were searched to identify relevant studies. A screening process, using a set of pre-determined inclusion criteria, identified 54 studies, with the strength of evidence and uncertainty for each study being assessed. A random effects meta-analysis was used to explore heterogeneity in relation to a number of factors, with a cumulative meta-analysis conducted to establish changes in WTP over time. The results indicated a small, positive WTP (0.63 standard deviations) for farm animal welfare varying in relation to a number of factors including animal type and region. Socio-demographic characteristics explained the most variation in the data. An evidence gap was highlighted in relation to reduced WTP for specific production diseases associated with the intensification of production, with only 4 of the 54 studies identified being related to this. A combination of market and government based policy solutions appears to be the best solution for improving farm animal welfare standards in the future, enabling the diverse public preferences to be taken into consideration.